2010
DOI: 10.1093/jac/dkq002
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin as an adjuvant to pegylated interferon and ribavirin in HIV/hepatitis C virus genotype 1 co-infected patients: an open-label randomized controlled study

Abstract: Fluvastatin addition to standard therapy did not significantly increase the SVR rate in HIV/HCV genotype 1 co-infected patients; however, it did significantly improve the RVR. Further studies are needed to confirm these promising results and to investigate the mechanisms of action of statins in HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Regarding the laboratory results, only one patient in group I showed a significant rise of ALT by week 24, for which he continued treatment by SOC therapy alone. This was similar to previous studies documenting the safe use of statins in HCVinfected patients without the risk of hepatotoxicity (23,(25)(26)(27)(28). Another patient discontinued treatment at week 28 because of retroperitoneal infection that was drained surgically.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the laboratory results, only one patient in group I showed a significant rise of ALT by week 24, for which he continued treatment by SOC therapy alone. This was similar to previous studies documenting the safe use of statins in HCVinfected patients without the risk of hepatotoxicity (23,(25)(26)(27)(28). Another patient discontinued treatment at week 28 because of retroperitoneal infection that was drained surgically.…”
Section: Discussionsupporting
confidence: 89%
“…EVR was negatively influenced by smoking (p=0.001) and positively related to low viral load and high ALT. Milazzo et al (23) found none of the patients' demographics or laboratory results to be correlated with SVR. Although Kondo et al (22) found male gender, high Hb, and high TLC to be associated with SVR in FLV-treated patients, Harrison showed that low HDL and high LDL levels influenced SVR (29).…”
Section: Discussionmentioning
confidence: 99%
“…Gower and Graham (26) reported that statins showed antiviral activity against RSV in vivo. The pharmacological potential of cholesterollowering drugs to curb virus infection has also been proposed and evaluated in hepatitis C virus with promising results in which statins significantly improved the rapid antiviral response caused by pegylated interferon in an open-labeled randomized controlled study (60). …”
Section: Figmentioning
confidence: 99%
“…properties such as antiviral (Bader et al, 2008;Bader and Korba, 2010;Jameson et al, 2010;Milazzo et al, 2010) and antitumor activities (Takahashi et al, 2006;Takahashi and Nishibori, 2007;Garwood et al, 2010), however the antitumor molecular mechanisms by which the statin block cancer cell growth are poorly understood (Ghosh-Choudhury et al, 2010), and there are emerging interests to explore the anticancer potentials of HMGCoA reductase inhibitors in the clinical setting, particularly in tumor sites sensitive to these agents in vitro (Chan et al, 2003), some mechanism proposes for anticancer activities are apoptotic inducer, antiangiogenic and antimetastatic. These properties are associates with the inhibition of the synthesis of isoprenoid intermediates of the mevalonate pathway (Slawinska and KandeferSzerszen, 2008 …”
Section: Introductionmentioning
confidence: 99%